2004
DOI: 10.1055/s-2004-815869
|View full text |Cite
|
Sign up to set email alerts
|

Feminizing Genital Reconstruction: Experience with 52 Cases of Ambiguous Genitalia

Abstract: The Hendren's techniques of flap vaginoplasty for low confluence and vaginal pull-through for high confluence offer satisfactory cosmetic and functional results. Long-term follow-up is necessary to ensure social and psychosexual adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 22 publications
2
6
0
1
Order By: Relevance
“…The age at presentation for these lesions in the present report did not differ from the findings of previous studies 4–7 . As this study and earlier reports have shown, there is a tendency for early presentation in most of these children.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The age at presentation for these lesions in the present report did not differ from the findings of previous studies 4–7 . As this study and earlier reports have shown, there is a tendency for early presentation in most of these children.…”
Section: Discussionsupporting
confidence: 55%
“…In some instances, they may be part of a multi‐organ anomaly 1–3 . Management of the lesions vary according to the aetiology with most cases responding to simple operative procedure 4–6 . On the other hand, disorders involving multiple organs, especially those resulting from persistent urogenital sinus and cloaca, provide daunting reconstructive challenges 1,3,6–8 …”
mentioning
confidence: 99%
“…In this type of reconstructive surgery a simple exteriorisation of a low vagina can reasonably be combined with the cosmetic correction of virilised external genitalia. For a higher degree of masculinisation the perineal pull-through vaginoplasty as described by Hendren and Donahoe 1980 is still one of the preferred operative techniques [1,5], but it is not the subject of our study.…”
Section: Introductionmentioning
confidence: 98%
“…The late results of feminizing genitoplasty have been systematically documented in the literature [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%